Cerebrovascular Events, Secondary Intracranial Tumors, and Mortality After Radiotherapy for Nonfunctioning Pituitary Adenomas: A Subanalysis From the Dutch National Registry of Growth Hormone Treatment in Adults - van Varsseveld, N. C.; van Bunderen, C. C.; Ubachs, D. H. H.; Franken, A. A. M.; Koppeschaar, H. P. F.; van der Lely, A. J.; Drent, M. L. (The journal of clinical endocrinology and metabolism, 2015)
Context:Radiotherapy is frequently administered as adjuvant treatment in patients with clinically nonfunctioning pituitary adenomas (NFPAs). However, concerns have been raised about potential long-term side effects, including cerebrovascular events (CVEs) and secondary intracranial tumors.Objective:The aim of this study was to analyze the risk of CVEs, secondary intracranial tumors, and mortality in irradiated (IRR) NFPA patients, compared with NFPA patients who were not irradiated (non-IRR).Design, Setting, and Patients:The study cohort included 806 patients with a NFPA from the Dutch National Registry of Growth Hormone Treatment in Adults, a nationwide long-term surveillance study in severe GH-deficient adult patients. IRR patients (n = 456) were compared with non-IRR patients (n = 350).Main Outcome Measures:CVEs, secondary intracranial tumors, and mortality were measured.Results:Sixty-nine subjects developed a CVE. In men, but not in women, the incidence of a CVE was significantly higher in IRR patients than in non-IRR patients (hazard ratio 2.99, 95% confidence interval 1.31–6.79). A secondary intracranial tumor developed in five IRR patients and two non-IRR patients. After adjustment for age, radiotherapy was not associated with mortality.Conclusions:The incidence of secondary intracranial tumors and mortality did not differ between IRR and non-IRR patients. However, a CVE was found significantly more frequently in IRR men but not in women. Further research into the long-term effects of cranial radiotherapy seems mandatory. The potential risks of radiotherapy have to be taken into account when radiotherapy is considered in NFPA patients, and long-term follow-up is recommended.